Autoimmune movement disorders with neuronal antibodies: an update - Balint, Bettina; Bhatia, Kailash P. (Current opinion in neurology, 2021)
Purpose of review The rapid developments in neuroimmunology reflect also on the field of movement disorders, where there is an ever expanding spectrum of new antibodies. This review focuses on the new neuronal antibodies, their clinical spectrum and recent pathophysiological insights. It gives an update on previous work about neuronal antibody-related movement disorders. Recent findings Phosphodiesterase 10A antibodies are a new marker of paraneoplastic chorea. Seizure-related 6 homolog like 2 antibodies are a differential diagnosis in atypical parkinsonism with cerebellar ataxia and cognitive impairment. mGluR5-antibodies cause various hyperkinetic movement disorders with Ophelia syndrome. Most new antibodies were described in the context of cerebellar ataxia: Kelch-like protein 11 antibodies are a comparatively frequent marker of paraneoplastic cerebellar ataxia with germ cell tumours. Nonparaneoplastic cerebellar ataxia occurs with Septin-5 and neurochondrin antibodies. Studies into the mechanisms of neuronal surface antibodies have shown that there is much pathophysiological heterogeneity, ranging from immediate antagonistic effect to induction of neurodegeneration after weeks. The new markers of autoimmune movement disorders are key to identify those patients that may benefit from immunotherapy, and tumour therapy, where appropriate. Insights into the underlying pathophysiology might guide treatment decisions and help tailoring more targeted approaches in the future.